Cargo Container Monitoring Data Reliability Evaluation in WSN Nodes - Jakovlev, S.; Andziulis, A.; Bulbenkiene, V.; Didziokas, R.; Bogdevicius, M.; Plestys, R.; Zakarevicius, R. (Elektronika ir Elektrotechnika, 2012)
The application of state-of-art mobile technologies in cargo container transportation monitoring systems (ex. Sensor networks) is possible only after assessing the reliability of data transfer. Data reliability depends on how accurately container state is evaluated by sensors and sensor reliability itself. Four probability values are introduced that define the states of damaged and undamaged containers and evaluate the generation of true and false data. The formats of messages that are being sent to the integrated network database are described. The definition of data defect level is introduced and used to evaluate the aggregate state of a node, consisting of a container and a sensor. The dependences of defect levels on the probabilities to detect false data at nearby nodes in the problem area have been derived. It enables real-time detection of data defects, thus helping during decision making processes in cargo transportation enterprise environment. Ill. 2, bibl. 4, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1371